Correlation between preoperative and postoperative miR-29c-3p level changes and immune response in paediatric acute septic appendicitis and its predictive significance for complications: a retrospective study - Li Hong; Baohui Yin; Chunsheng Duan; Lixia Zhou; Yingxuan Huang (Italian Journal of Pediatrics)
Abstract Background Postoperative complications in children with acute suppurative appendicitis (ASA) can lead to very serious consequences. In this study, we investigated the pre- and postoperative expression of miR-29c-3p in ASA and its value in predicting postoperative complications. Methods Retrospectively, 128 children with ASA and 93 healthy children were included. The qRT-PCR technique was used to detect miR-29c-3p expression in children with ASA preoperatively and 24 h postoperatively. The levels of immune cells (WBC, NEU, LYM) were detected by routine blood test, and the levels of immune proteins CRP and inflammatory factors (TNF-α and IL-6) were detected by ELISA. Results Before surgery, children with ASA had higher levels of miR-29c-3p than healthy controls. But after surgery, miR-29ac-3p levels dropped a lot in children with ASA. The serum levels of immune cells (WBC, NEU, LYM), immune protein CRP and inflammatory factors (TNF-α and IL-6) were significantly decreased in children with ASA. Postoperative miR-29c-3p levels were positively correlated with the levels of immune indicators. The patients with higher miR-29c-3p expression levels showed a greater incidence of postoperative complications. Conclusions The expression of miR-29c-3p was positively correlated to immune cells, immune proteins, and inflammatory factors. The expression levels of miR-29c-3p were related to the occurrence of postoperative complications and could, therefore, be utilized to predict the occurrence of postoperative complications in children with ASA.